Efficacy of practical stump treatment in Latvia - Skola, Uvis (SLU/Southern Swedish Forest Research Centre, 2019)
Root and butt rot caused by Heterobasidion spp. result in severe economic losses in Norway spruce forests of the northern hemisphere. Stump treatment using biological or chemical control agents are amongst the most effective solutions of limiting introduction of Heterobasidion spp. after tree felling. The aims of my thesis were to test the control efficacy of Rotstop®, native Latvian Phlebiopsis gigantea strain and urea as a control agent against natural spore infection of Heterobasidion spp. on pre-commercial thinning stumps of Norway spruce and to develop the methodology to increase the efficacy of control agents. Sample plots in three Norway spruce stands located in eastern part of Latvia were pre-commercially thinned. In search of improved efficacy of control agents, two methods of preventing primary infection by Heterobasidion spp. were compared. First method concerned practical stump treatment with a control agent while according to second method protective cover (wooden disc) was placed on half of the stumps in each sample plot after treatment was applied. After 14 weeks a total of 476 sample discs were obtained and later on analysed. Results concerning presence and magnitude of infection were not influenced by sample plot. All treatments within a method showed lower infection rates than corresponding control stumps. 35 % of not covered control stumps were infected with a mean relative infection area of 3.4 %. Infection frequency for treated stumps ranged from 13-18 % with a mean relative infected area ranging from 0.9 to 1.1 %. Infection rates for covered control and urea-treated stumps were higher but for native Latvian P. gigantea and Rotstop®-treated stumps it was lower compared to their not covered counterparts. Control efficacy in terms of reduced relative area of infection was similar for all treatments when stumps were not covered. When stump surface was covered, Latvian P. gigantea and Rotstop® showed greater values than urea (96 %, 99 % and 73 % respectively). Stump treatment using Rotstop®, native Latvian P. gigantea strain or urea as a control agent should be considered since all treatments significantly reduce the primary infection rate of Heterobasidion spp.